Rethinking the security issue in the China-Burma territorial dispute. Issue 1 (2nd January 2023) - Fan, Hongwei; Zou, Yizheng
ABSTRACT: This article challenges the dominant friendship-oriented scholarship on the China-Burma border in China and revisits the nature of China's compromise with Burma in the territorial disputes between 1956 and 1960. Multi-archival and multi-lingual primary sources including official archives and memoirs from Burma, China, the United States and the United Kingdom, are extensively used. In particular, Chinese local archives are used for the first time to demonstrate a new picture of the CCP's decision-making process in formulating policies of territorial compromise with Burma. Beijing was willing to offer concessions to Burma in the border dispute to improve its own national security because of the security vacuum in the China-Burma border region, Burma's commitments to China, and the area's critical geopolitical value.